O conceito de comportamento autoclítico na obra de B. F. Skinner: uma investigação histórico-conceitual - Prado, Haline Zuquim Aidar (2024)
Considering that several bibliographical reviews indicate the existence of few empirical studies that investigate autoclitic behavior; that it is an important concept that presents a inherent complexity to the phenomenon addressed; and the intricate and distributed way that Skinner developed to write about the subject in his book Verbal Behavior, the present study had as objective to elucidate the definition of autoclitic behavior elaborated by B. F. Skinner through the historical-conceptual analysis of the concept in the author's work. Keywords were searched in two hundred and thirty-five digitally available works by Skinner, from which sixty-two publications that addressed the subject autoclitic behavior were selected. The reading in chronological order of the works, as well as the reading, in full, of Parts IV and V of Verbal Behavior, were guided by the following categories of analysis: (a) Terminologies of autoclitic behavior; (b) Control Variables and Characteristics of Response Classes Typically Involved in Autoclitic Behavior; (c) Types of Autoclitic Behavior; (d) Autoclitic Behavior and Traditional Formulations; and (e) Autoclitic Behavior and Practice Questions. Among the results, the present study seems to have managed to clarify the definition of autoclitic behavior, explaining the elements that constitute the contingency of reinforcement of this type of behavior, hoping to contribute to a better understanding of the conceptual system of behavior analysis. Discussions about other authors definitions of autoclitic behavior and suggestions for future studies were made